2019
DOI: 10.1021/acs.inorgchem.9b00758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystal Water on Crystal Structure, Electronic Structure, Band Structure, and Charge Separation of WO3·2H2O Nanosheets

Abstract: In this work, we mainly investigate the influence of structure water on crystal structure, electronic structure, band structure, and charge separation of WO3·2H2O. It is found, for the first time, that although water is a weak electron donor, a ligand-to-metal charge transfer (LMCT) from H2O to W occurs. The structure water contributes to the conduction band (CB) of WO3·2H2O, and the band gap of WO3·2H2O is obviously narrowed, thus increasing the light absorption obviously. Moreover, the results of EIS, photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This value was about 0.60 eV smaller than the experimental result, which was due to the electron delocalization error in the generalized gradient approximation (GGA)-Perdew-Burke-Ernzerhof (PBE) method. 33,[52][53][54][55] Compared with native TiO 2 , the calculated conduction band and the valence band of S-TiO 2 had 0.19 eV and 0.70 eV upward shifts, respectively, which led to a significant reduction (0.51 eV) in the energy band gap of S-TiO 2 . These results were consistent with the upward shift of the valence band and the more negative conduction band potential of S-TiO 2 measured by the electrochemical experiments.…”
Section: Mechanism Of Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…This value was about 0.60 eV smaller than the experimental result, which was due to the electron delocalization error in the generalized gradient approximation (GGA)-Perdew-Burke-Ernzerhof (PBE) method. 33,[52][53][54][55] Compared with native TiO 2 , the calculated conduction band and the valence band of S-TiO 2 had 0.19 eV and 0.70 eV upward shifts, respectively, which led to a significant reduction (0.51 eV) in the energy band gap of S-TiO 2 . These results were consistent with the upward shift of the valence band and the more negative conduction band potential of S-TiO 2 measured by the electrochemical experiments.…”
Section: Mechanism Of Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…The crystalline structure of WO 3 is described as a 3D network of WO 6 octahedral with shared edges and corners interconnected by weak van der Waals force (shown in Figure 4). [ 23‐24 ] This unique structure provides open tunnels for photon and electron channels and the construction of monoclinic crystalline. Depending on the unit‐cell axis, the chevron patterns constructed by octahedral framework exhibit some octahedral site twists.…”
Section: Property Of Wo3 Iopcsmentioning
confidence: 99%
“…The crystal structures of WO 3 (Reproduced with permission from ref. [24]. Copyright 2016 The Royal Society of Chemistry.…”
Section: Property Of Wo3 Iopcsmentioning
confidence: 99%
“…Liu et al reported the excellent photocatalytic activity of a mixed-phase o/m-WO 3 ·H 2 O compared to the pure m-WO 3 and o-WO 3 ·H 2 O phases . Shi et al studied the contribution of water content in the structure of o-WO 3 ·2H 2 O nanosheets in the degradation of MB …”
Section: Introductionmentioning
confidence: 99%
“…13 Liu et al reported the excellent photocatalytic activity of a mixedphase o/m-WO 3 •H 2 O compared to the pure m-WO 3 and o-WO 3 •H 2 O phases. 17 27 Recently, efforts have been devoted to synthesizing colored WO 3 with an extended absorption tail covering the visible and a near-infrared (NIR) window of the light spectrum. report by Bechinger et al shows an increase in WO 3 coloration efficiency by 40% as the oxygen content decreases from 50 to 5%.…”
Section: Introductionmentioning
confidence: 99%